Dielectric variations of barium titanate additions on mullite- kaolinite sample - See, Alex; Hassan, Jumiah; Hashim, Mansor; Wan Yusoff, Wan Mohamad Daud (Malaysian Solid State Science and Technology Society, 2008)
This research was designed to form better dielectric composite material using one steady state dielectric with a good dielectric material. Distinct dielectric composites were successfully produced using locally sourced kaolinite clay. The samples were made using kaolinite as the base matrix and Barium Titanate (BT) added at varying ratios. Barium Titanate was synthesized via solid-state reaction using Barium Carbonate and rutile Titanium (IV) Oxide sintered at 1300°C. Local white kaolinite was used as the matrix at varying weight ratios. The powders were dry-mixed and made into pellets for calcination at 1000°C. The dielectric measurements were carried out using HP 4291B Impedance Analyzer dielectric setup. Three samples were prepared, namely 50%BT, 60%BT, and 70%BT. The dielectric measurements were carried out in an LT furnace at temperatures 30°C - 400°C with frequencies ranging from 10 Hz to 1 MHz. Measurements showed varying ionic relaxation for all samples.